Golli myelin basic proteins modulate voltage-operated Ca(++) influx and development in cortical and hippocampal neurons - Cheli, VT (Mol Neurobiol, 2015)
The golli proteins, products of the myelin basic protein gene, are widely expressed in oligodendrocyte progenitor cells and neurons during the postnatal development of the brain. While golli appears to be important for oligodendrocyte migration and differentiation, its function in neuronal development is completely unknown. We have found that golli proteins function as new and novel modulators of voltage-operated Ca(++) channels (VOCCs) in neurons. In vitro, golli knock-out (KO) neurons exhibit decreased Ca(++) influx after plasma membrane depolarization and a substantial maturational delay. Increased expression of golli proteins enhances L-type Ca(++) entry and processes outgrowth in cortical neurons and pharmacological activation of L-type Ca(++) channels stimulates maturation and prevents cell dead in golli-KO neurons. In situ, Ca(++) influx mediated by L-type VOCCs was significantly decreased in cortical and hippocampal neurons of the golli-KO brain. These Ca(++) alterations affect cortical and hippocampal development and the proliferation and survival of neural progenitor cells during the postnatal development of the golli-KO brain. The CA1/3 sections, and the dentate gyrus of the hippocampus were reduced in the golli-KO mice as well as the density of dendrites in the somatosensory cortex. Furthermore, the golli-KO mice display abnormal behavior including deficits in episodic memory and reduced anxiety. Because of the expression of the golli proteins within neurons in learning and memory centers of the brain, this work has profound implication in neurodegenerative diseases and neurological disorders.